The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1093/milmed/162.11.749
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Radiography in Small Bowel Obstruction: A Prospective, Randomized Trial

Abstract: Small bowel obstruction is a common cause of acute abdominal distress, accounting for up to 20% of emergency admissions to surgical services. Although the majority of obstructions will resolve with conservative therapy alone, there are currently no reliable tests for identifying the patients who will require operation. Barium contrast studies have the potential to rapidly identify patients with complete small bowel obstruction, but many surgeons are hesitant to use them for fear of inducing complications. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…After review of full‐length manuscripts, 20 studies were found to be potentially eligible. Of these, six were subsequently excluded: two randomized patients to either Gastrografin ® (Schering, Berlin, Germany) or Omnipaque ™ 22, 23, one used barium as the contrast agent24, one randomized patients to either Gastrografin ® or surgery25 and two were duplicate studies26, 27. Seven studies were included in the evaluation of the diagnostic role of WSCA3–9 and nine in the assessment of its therapeutic role7, 8, 10–16.…”
Section: Resultsmentioning
confidence: 99%
“…After review of full‐length manuscripts, 20 studies were found to be potentially eligible. Of these, six were subsequently excluded: two randomized patients to either Gastrografin ® (Schering, Berlin, Germany) or Omnipaque ™ 22, 23, one used barium as the contrast agent24, one randomized patients to either Gastrografin ® or surgery25 and two were duplicate studies26, 27. Seven studies were included in the evaluation of the diagnostic role of WSCA3–9 and nine in the assessment of its therapeutic role7, 8, 10–16.…”
Section: Resultsmentioning
confidence: 99%
“…An enteroclysis study is a modification of the small bowel follow through in which the duodenum is first intubated under fluoroscopy and contrast injected under pressure. This study is highly reliable for both cases, of low and high-grade obstruction because it bypasses the stomach where washout of contrast can occur [13][14][15][16]. Although modern CT technology has significantly contributed to the determination of the PC score, it is a relatively static technology, unable to accurately observe the bowel movement and dynamic distribution of the small intestine.…”
Section: Diagnostic Methods Commonly Used In the Preoperative Estimatmentioning
confidence: 99%
“…Most common findings are dilated small intestine loops, colonic distention, multiple air-fluid levels, and foreign bodies or gallstones. In more complicated cases, further diagnostic evaluations may be necessary [10,11].…”
Section: Laboratory and Radiologic Examinationsmentioning
confidence: 99%